2023
DOI: 10.1101/2023.01.11.523441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic DNA methylation turnover at the exit of pluripotency epigenetically primes gene regulatory elements for hematopoietic lineage specification

Abstract: Epigenetic mechanisms govern developmental cell fate decisions, but how DNA methylation coordinates with chromatin structure and three-dimensional DNA folding to enact cell-type specific gene expression programmes remains poorly understood. Here, we use mouse embryonic stem and epiblast-like cells deficient for 5-methyl cytosine or its oxidative derivatives (5-hydroxy-, 5-formyl- and 5-carboxy-cytosine) to dissect the gene regulatory mechanisms that control cell lineage specification at the exit of pluripotenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Several studies have evaluated the impact of global perturbation of 5mC levels during early embryonic development. In support of this model, all of them found that stem cells with altered 5mC levels are nevertheless competent to differentiate into multiple cell lineages [72–75]. Yet, they observed altered distribution of cell types within embryos, indicating that 5mC may indeed contribute to accurate cell fate determination [73,75].…”
Section: Functional Relevance Of Tf‐binding Modulation By 5mc At Enha...mentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have evaluated the impact of global perturbation of 5mC levels during early embryonic development. In support of this model, all of them found that stem cells with altered 5mC levels are nevertheless competent to differentiate into multiple cell lineages [72–75]. Yet, they observed altered distribution of cell types within embryos, indicating that 5mC may indeed contribute to accurate cell fate determination [73,75].…”
Section: Functional Relevance Of Tf‐binding Modulation By 5mc At Enha...mentioning
confidence: 96%
“…Yet, they observed altered distribution of cell types within embryos, indicating that 5mC may indeed contribute to accurate cell fate determination [73,75]. Moreover, within specific cell identities, altered methylation deregulated the precise establishment of gene expression programmes [72–75]. Importantly, most of the epigenetic and chromatin accessibility changes observed in these mutants occurred at enhancers, supporting the idea that 5mC may control the activity of some of them.…”
Section: Functional Relevance Of Tf‐binding Modulation By 5mc At Enha...mentioning
confidence: 97%